Izpodbojnost sklepa o izključitvi manjšinskih delničarjev zaradi kršitve pravice do obveščenosti - Podgorelec, Peter (Podjetje in delo, 2024)
In case law, there are different standpoints on whether an excluded shareholder can challenge the general meeting’s resolution on exclusion if they did not receive complete and correct answers to the questions about the offered monetary compensation at the general meeting. The author supports the position that the exclusion of contestability due to the reasons stated in the first paragraph of Article 388 of the Companies Act - ZGD-1 (the monetary compensation was not appropriate or not offered at all or not offered correctly) also includes the exclusion of contestability due to insufficient information if it relates to monetary compensation. Despite the possibility of such an interpretation based on an argumentum a fortiori, the author believes that, due to the various viewpoints in case law, explicit legal regulation of this issue would be sensible not only within the framework of the exclusion procedure but for all cases of corporate transactions where a special judicial procedure for assessing the adequacy of compensation is envisaged. The author therefore proposes a legislative solution modelled on German and Austrian corporate law.
Keywords: contestability of the general meeting’s resolution; denarna odpravnina; exclusion of minority shareholders (squeeze-out); izključitev manjšinskih delničarjev; izpodbojnost sklepa skupščine; monetary compensation; pravica do obveščenosti; the right to access information